Understanding the taxonomic homogenization of road-influenced plant assemblages in the Qionglai mountain range: A functional and phylogenetic perspective - Li, Honglin; Luo, Peng; Yang, Hao; Xie, Wenwen; Luo, Chuan; Jia, Honghong; Cheng, Yue; Huang, Yu (Frontiers in Plant Science, 2023)
As an increasingly prevalent form of human activity, roads drive the taxonomic homogenization of plant assemblages, threatening global biodiversity. However, little is known about how roads will impact FBD and PBD and how these effects relate to taxonomic homogenization. To understand the mechanism of taxonomic homogenization triggered by mountain road, we used species absence/presence data from 76 plots and values for 12 traits measured on 978 species from the interior and roadside communities in the Qionglai mountain range, one of the temperate regions with the highest plant species richness in the world. We used SEM to consider several surrogates of road disturbance and the causal relationship between three aspects of beta diversity; we assumed that the environmental changes primarily affect FBD and then regulate the changes in TBD and PBD. Meanwhile, we hypothesized that there is also a causal relationship between PBD and TBD. Moreover, we considered the responses of PBD at different evolutionary depths to roads. Our findings suggest that the convergence of species composition at the landscape scale arise by a combination of adaptive responses of the functional traits of organism and sorting or assembly of clades drawn from the regional lineage pools to environmental stress.